Management of a traumatic anorectal full-thickness laceration: a case report - Laura Fortuna; Andrea Bottari; Riccardo Somigli; Sandro Giannessi (Journal of Trauma and Injury)
The rectum is the least frequently injured organ in trauma, with an incidence of about 1% to 3% in trauma cases involving civilians. Most rectal injuries are caused by gunshot wounds, blunt force trauma, and stab wounds. A 46-year-old male patient was crushed between two vehicles while he was working. He was hemodynamically unstable, and the Focused Assessment with Sonography for Trauma showed hemoperitoneum and hemoretroperitoneum; therefore, damage control surgery with pelvic packing was performed. A subsequent whole-body computed tomography scan showed a displaced pelvic bone and sacrum fracture. There was evidence of an anorectal full-thickness laceration and urethral laceration. In second-look surgery performed 48 hours later, the pelvis was stabilized with external fixators, and it was decided to proceed with loop sigmoid colostomy. A tractioned rectal probe with an internal balloon was positioned in order to approach the flaps of the rectal wall laceration. On postoperative day 13, a radiological examination with endoluminal contrast injected from the stoma after removal of the balloon was performed and showed no evidence of extraluminal leak. Rectosigmoidoscopy, rectal manometry, anal sphincter electromyography, and trans-stomic transit examinations showed normal findings, indicating that it was appropriate to proceed with the closure of the colostomy. The postoperative course was uneventful. The optimal management for extraperitoneal penetrating rectal injuries continues to evolve. Primary repair with fecal diversion is the mainstay of treatment, and a conservative approach to rectal lacerations with an internal balloon in a rectal probe could provide a possibility for healing with a lower risk of complications.